The contemporary Quranist movement in Bangladesh and its principal arguments: an analytical study - Nasrullah, Hamed; Nik Abdullah, Nik Md. Saiful Azizi; Abdur Rashid, Mohammad Abdullah (Banglavision, 2026)
This study investigates the contemporary Quranist movement in Bangladesh, examining its intellectual foundations, principal arguments, and core objections to the authority of the Prophetic Sunnah. It offers a systematic analytical and critical evaluation of these claims within the normative framework of the Qur’an, the Sunnah, and the methodological principles of Ahl al-Sunnah wa al-Jamāʿah. The significance of this research arises from the growing tendency within certain intellectual and media circles in Bangladeshi society to advocate exclusive adherence to the Qur’an while rejecting or marginalizing the binding authority of the Sunnah. Such tendencies carry far-reaching intellectual, theological, and social implications, particularly with respect to Islamic identity and the unity of religious authority among Muslims. Methodologically, the study adopts an inductive and foundational approach to examine the writings and public statements of prominent Quranist figures. This is followed by an analytical and critical framework that classifies and evaluates their arguments, identifies internal inconsistencies, and responds through both textual evidence and rational analysis. The research further incorporates a contextual case study exploring the dissemination of Quranist thought in Bangladesh and its impact on youth and university students. The study concludes that exclusive reliance on the Qur’an coupled with the denial of the Sunnah’s authority does not represent a methodologically sound or academically sustainable position. Rather, it reflects fundamental misunderstandings concerning the nature of revelation and its interpretive framework. The findings affirm that an accurate comprehension of the Qur’an and the coherent implementation of Islamic law are inseparable from the explanatory and practical role of the Prophetic Sunnah. Finally, the study underscores the potential implications of this trend for religious cohesion and social stability, and it proposes scholarly and educational recommendations to strengthen sound Islamic understanding and address contemporary intellectual challenges in Bangladesh.